2019
DOI: 10.1038/s41598-018-36983-z
|View full text |Cite
|
Sign up to set email alerts
|

Genome analysis of a thermophilic exopolysaccharide-producing bacterium - Geobacillus sp. WSUCF1

Abstract: Geobacillus sp. WSUCF1 is a Gram-positive, spore-forming, aerobic and thermophilic bacterium, isolated from a soil sample obtained from a compost facility. Strain WSUCF1 demonstrated EPS producing capability using different sugars as the carbon source. The whole-genome analysis of WSUCF1 was performed to disclose the essential genes correlated with nucleotide sugar precursor biosynthesis, assembly of monosaccharide units, export of the polysaccharide chain, and regulation of EPS production. Both the biosynthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 73 publications
(90 reference statements)
0
19
0
Order By: Relevance
“…In addition, UDP-glucose 4-epimerase and mannose-1-phosphate guanylyltransferase, identified in Geobacillus sp. WSUCF1 [108], were also detected in strain EC-3.…”
Section: Discussionmentioning
confidence: 91%
“…In addition, UDP-glucose 4-epimerase and mannose-1-phosphate guanylyltransferase, identified in Geobacillus sp. WSUCF1 [108], were also detected in strain EC-3.…”
Section: Discussionmentioning
confidence: 91%
“…The 10-day growth profile indicated highest activity of laccase in supernatant on day six (460 IU/L), endoxylanase on day eight (270 IU/L), and endoglucanase on day ten (110 IU/L). A data mining exercise revealed the presence of genes encoding for hemicellulases (xylan 1,4-β-xylosidase, endo-1,4-β-xylanase, and xylan α-1,2-glucuronosidase), cellulases (endoglucanases, -glucosidases) and amylases in the genome of strain WSUCF1 28 , 30 32 . We observed that these enzymes displayed stable activity even after 10 days of the prolonged exposure at 60 O C, corroborating the thermostability of these enzymes, as reported in previous studies 33 , 34 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The methods used for measuring the enzyme activities are given in the supplementary information. The enzyme assay studies revealed cellulase, hemicellulases and laccase in the WSUCF1 cultures ( www.nature.com/scientificreports/ cellulases (endoglucanases, -glucosidases) and amylases in the genome of strain WSUCF1 28,[30][31][32] . We observed that these enzymes displayed stable activity even after 10 days of the prolonged exposure at 60 O C, corroborating the thermostability of these enzymes, as reported in previous studies 33,34 (Fig.…”
Section: Versatility Of Geobacillus Sp Strain Wsucf1 In Mfcsmentioning
confidence: 99%
See 1 more Smart Citation
“…Geobacillus sp. strain WSUCF1, a thermophilic microbe obtained from the compost pile in Washington State University, Pullman, Washington, USA (46.7319 • N, 117.1542 • W), is one such bacterium that produces highly thermostable lignocellulose deconstruction enzymes when grown on unprocessed lignocellulosic substrates, such as corn stover and prairie cordgrass [9,10]. WSUCF1 strain is highly efficient in depolymerizing unprocessed lignocellulose, needing no preprocessing/pretreatment of the biomasses; hence, utilization of WSUCF1 as a whole cell, or even its cells extract (for enzyme cocktails), is an attractive target for thermophilic bioprocessing of lignocellulosic biomasses.…”
Section: Introductionmentioning
confidence: 99%